The role of reactive oxygen species metabolism-related genes in mediating cisplatin resistance in ovarian clear cell carcinoma - Deng, Wen; Jingwu Wu; Xiaohui Wang; Na Zhao; Hu, Kai; Fu, Minglei (Journal of the Pakistan Medical Association, 2026)
Cisplatin resistance in ovarian cancer, particularly in ovarian clear cell carcinoma, involves intricate mechanisms related to oxidative stress, deoxyribonucleic acid repair, and cell cycle. Resistance in ovarian clear cell carcinoma is associated with genes, such as pyruvate dehydrogenase kinase-2 and hepatocyte nuclear factor 1 beta, which enhance glycolysis and reduce reactive oxygen species that would normally facilitate cisplatin-induced deoxyribonucleic acid damage. Additionally, nuclear factor erythroid 2-related factor-2 and superoxide dismutase-2 play pivotal roles in regulating reactive oxygen species levels, thereby safeguarding ovarian clear cell carcinoma cells from oxidative damage. The postsynaptic density protein 95/discs large/zona occludens-1 (PDZ)-binding motif-angiopoietin-like 4-nicotinamide adenine dinucleotide phosphate oxidase-2 axis plays a crucial role in modulating ferroptosis, presenting potential therapeutic targets. A deeper understanding of these mechanisms offers promising strategies to overcome cisplatin resistance, particularly in ovarian clear cell carcinoma. These insights could pave the way for targeted therapies aimed at improving ovarian cancer outcomes, especially for ovarian clear cell carcinoma subtypes. Key Words: Reactive oxygen species, Ovarian neoplasms, Drug resistance, Neoplasm.